Temporal analysis of national level Muay-Thai matches: Effects of competitive phase (Revista de Artes Marciales Asiáticas, 2015)
Introduction: Temporal analysis of matches allows the study of fighting patterns in combat sports. With this procedure, we can recreate the efforts in specific training. However, up to date have no information concerning temporal analysis considering competitive level in Muay-Thai. Objective: To investigate temporal characteristics of Muay-Thai athletes in official competition from national level, considering round, and to compare preliminary combats with those that had medal disputes. Material and methods: Were recorded 65 matches in a Brazilian championship. We conducted in loco recording. To time-motion analysis, Software Kinovea™ was used. Were considered Observation, Preparation and Interaction periods, as well as high intensity and low intensity ratio (HI:LI). The average duration of the rounds between competitive phases (preliminary or finals) was compared with a t test. A generalized linear model was applied considering effort duration as dependent variable and competitive level, round and effort type as independent. Significant level was set in 5%. Results: Were registered 7 to 8 s of Observation, near from 3 s of Preparation and 4 to 5.5 s of Interaction effort type, and the duration of Observation effort was significantly superior the others. Significant differences were observed in the Interaction between preliminary and finals (respectively 5.5 ± 0.3 s and 3.7 ± 0.5 s; p < 0.05). Pooling the Observation and Preparation time as low intensity (LI), and Interaction as high intensity (HI) efforts, the HI:LI ratio was 1:2in eliminatory and 1:3 in the final matches. Conclusions: Muay-Thai is an intermittent combat sport, the duration of Interaction effort type is lower in final in comparison to preliminary matches.